A study of some discrete Dirac equations with principal functions - Koprubasi, T.; Mohapatra, R. N. (Springer Science and Business Media LLC, 2016)
zbMATH Open Web Interface contents unavailable due to conflicting licenses.
Keywords: Time-dependent Schrödinger equations and Dirac equations; Particular ordinary differential operators (Dirac, one-dimensional Schrödinger, etc.); eigenvalue; principal function; Difference operators; General spectral theory of ordinary differential operators; discrete Dirac equation; spectral analysis